Analisis Perilaku Konsumen Muslim Terhadap Akad Jual Beli Istishna Dalam Ekonomi Islam - Shabrina Az Zahra (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Consumer behavior is a condition where consumers choose, buy and utilize products/services to fulfill their needs or desires. Consumer behavior according to Islam is comprehensive and prioritizes ethics, starting from selecting goods to their use and finally the benefits obtained from the goods consumed. Buying and selling (business) in society is a routine activity carried out all the time by all humans. However, not all Muslims carry out correct buying and selling according to Islamic law. Istishna' can be referred to as a contract that is in place between the producer of an item or something similar and the orderer, who is the first party, allowing the producer to produce the item the first party wants at a price that is mutually agreed upon. In society, buying and selling (business) is a daily activity that all people engage in. But not all Muslims follow Islamic law when it comes to purchasing and selling. Some people are completely unaware of the rules outlined by Islamic law on purchasing and selling (commerce). Islamic law is derived from the Qur'an and Hadith, which contain numerous instances and guidelines for proper business practices. Muslim